Peritoneal dialysis and peritoneal fibrosis: molecular mechanisms, risk factors and prospects for prevention - N. Stepanova; L. Snisar; O. Burdeyna (Ukrainian Journal of Nephrology and Dialysis, 2022)
Peritoneal dialysis (PD) leads to structural and functional changes in the peritoneal membrane, the endpoint of which is peritoneal fibrosis. Peritoneal fibrosis is diagnosed in 50% and 80% of PD patients within 1 and 2 years of treatment initiation, respectively. A key role in the development of peritoneal fibrosis is played by mesothelial-mesenchymal transformation, a complex biological process of transition from mesothelium to mesenchyme. This review summarizes the current knowledge on the changes in peritoneal function and morphology, the molecular mechanisms of peritoneal fibrosis development, and its clinical consequences during PD. Special attention is given to established and potential risk factors for peritoneal fibrosis, and existing prevention strategies are considered.